Excellent color quality of phosphor converted white light emitting diodes with remote phosphor geometry - Thinh Cong Tran; Nguyen Doan Quoc Anh; Nguyen Thi Phuong Loan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
The remote phosphor structure is disadvantageous in color quality but more convenient in luminous flux when compared to conformal phosphor or in-cup phosphor structure. From this disadvantage, there are many studies to improve the color quality of the remote phosphor structure. This research will propose a dual-layer remote phosphor structure to improve color rendering index (CRI) and color quality scale (CQS) of WLEDs. The WLED package with color temperature of 8500 K is utilized in this study. The idea of the study is to locate a layer of phosphor green Y2O2S:Tb3+ or red ZnS:Sn2+ on the yellow phosphor YAG:Ce3+ film, and then finding the suitable added concentration of ZnS:Sn2+ to match the highest color quality. The results showed that ZnS:Sn2+ brings great benefits to increase CRI and CQS. The greater the ZnS:Sn2+ concentration is, the higher the CRI and CQS become owing to the rise in red light components in WLEDs. Meanwhile, the green Y2O2S:Tb3+ phosphor brings benefits to luminous flux. However, the decrease in luminous flux and color quality occurs when the concentration of ZnS:Sn2+ and Y2O2S:Tb3+ exceeds the corresponding level. This is proved by applying Mie-scattering theory and Lambert-Beer's law. The results of articles are important for WLEDs’ fabrication having higher white light quality.